Organizational behavior managing people and organizations - Griffin, Ricky W. (Houghton Mifflin Company, 2007)
Presenting a "psychology" course in the business curriculum, this text covers topics such as, individual motivation, leadership and interpersonal dynamics, and organisation design and culture. It is useful for undergraduate and graduate level students.